Study guides

Q: What is 27 minus 9 minus 6?

Write your answer...

Submit

Related questions

-18 minus 9 is -27

50 - 27 - 14 = 9

6/9 minus 6/9 = Zero.

-14 - 4 - 9 = -27

The numbers are: 6 plus square root of 27 and 6 minus square root of 27

27/9 = 3 x 2 = 6 + 8 - 3 = 11

It is 9*6 minus 7 = 47

27

27/12 - (9 x 9) = -78.75

It is -6 minus -9 = +3. That's because minus -9 is the same as +9.

9 - 6 = 3

6

-9

9

-15 minus -6 is -9

x2 - 6x - 27 = (x-9)(x+3)

(z-9)(z+3

5 x 6 - 9 - 4 = 17

2/9 minus 5/27 = 1/27

15

-9 - 6 = -15

27* 6/9 = (27*6)/9 = 3*6 [dividing numerator and denominator by 9] = 18

9 / (-1/3) = -27

27. 2+7=9 then minus 4. Next is plus 8 minus 3. Plus 9 minus 2. Plus 10 (27). Next is minus 1 which would be 26.

the answer two 9 and one eighth minus 6 and three fourths is